Comparison of 3D confromal radiotherapy and intensity modulated radiotherapy with or without simultaneous integrated boost during concurrent chemoradiation for locally advanced head and neck cancers. - Michael T Spiotto; Ralph R Weichselbaum (PLoS ONE)
Objective Radiotherapy techniques have evolved from 3D conformal radiotherapy (3D-CRT) to intensity modulated radiotherapy (IMRT) where boost fields are delivered either sequentially (IMRTseq) or with a simultaneous integrated boost (IMRT+SIB). Our goal was to compare the outcomes of patients treated with IMRT+SIB to traditional standards. Methods We analyzed the efficacy and toxicity of patients treated with concurrent chemoradiation using 3D-CRT, IMRTseq or IMRT+SIB. Between 1993 and 2012, 379 patients with non-metastatic Stage III-IV head and neck squamous cell cancer were treated with concurrent chemoradiation using 3D-CRT (n = 125), IMRTseq (n = 120) and IMRT+SIB (n = 134). Results Patients treated with any technique had similar rates of 2y local control, 2y regional control, 2y progression free survival and 2y overall survival. Patients treated with IMRT+SIB had lower rates acute toxicity according to Grade 3 or greater mucositis (3D-CRT: 44.0% vs. IMRTseq: 36.7% vs. IMRT+SIB: 22.4%; P<.0001), dermatitis (3D-CRT: 44.0% vs. IMRTseq: 20.0% vs. IMRT+SIB: 7.5%; P<.0001) and feeding tube placement during radiotherapy (3D-CRT: 80.0% vs. IMRTseq: 50.8% vs. IMRT+SIB: 44.0%; P<.0001) as well as late toxicity as measured by feeding tube use (P<.0001) and tracheostomy use (P<.0001). On multivariate analysis, IMRT+SIB predicted for less mucositis, dermatitis and feeding tube use compared to 3D-CRT and for less dermatitis compared to IMRTseq. Conclusions Compared to 3D-CRT and IMRTseq, IMRT+SIB provided similar outcomes and potentially less toxicity indicating it is a feasible technique for chemoradiation in locally advanced head and neck cancer.